1990
DOI: 10.1007/bf02433797
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic morphology of the temporomandibular joint in growing and mature crab-eating monkeys (Macaca fascicularis): the condylar articular layer

Abstract: In an attempt to establish maturational alterations in the morphology of the articular tissue layer, mandibular condyles of four immature and four mature male monkeys (Macaca fascicularis) were studied using light microscopy as well as scanning and transmission electron microscopy. Specimens were fixed in situ by perfusion in the presence of ruthenium red to stabilize proteoglycans. Preparations intended for observation in the scanning electron microscope were first dehydrated and sputtered for the examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Table 2 summarizes available data for the fiber/fibrils diameters. Regarding orientation, previous microscopic structural investigations of the condylar cartilage indicated that the collagen fibers in the fibrous zone appear to run predominately parallel to the surface but not to each other, forming sheet-like structures (de Bont et al, 1984;Klinge, 1996;Luder and Schroeder, 1990;Mizuno et al, 1990;Shibata et al, 1991), indicating a transversely isotropic fiber orientation. However, in a recent macroscopic investigation of the condylar cartilage, an anisotropic fiber orientation in the fibrous zone of porcine condylar cartilage was observed via polarized light, where the predominant orientation of collagen fibers was in the anteroposterior direction , which coincides well with the mechanical anisotropy of the tissue (Kang et al, 2000a;Singh and Detamore, 2008).…”
Section: Organization and Distribution Of Collagenmentioning
confidence: 93%
“…Table 2 summarizes available data for the fiber/fibrils diameters. Regarding orientation, previous microscopic structural investigations of the condylar cartilage indicated that the collagen fibers in the fibrous zone appear to run predominately parallel to the surface but not to each other, forming sheet-like structures (de Bont et al, 1984;Klinge, 1996;Luder and Schroeder, 1990;Mizuno et al, 1990;Shibata et al, 1991), indicating a transversely isotropic fiber orientation. However, in a recent macroscopic investigation of the condylar cartilage, an anisotropic fiber orientation in the fibrous zone of porcine condylar cartilage was observed via polarized light, where the predominant orientation of collagen fibers was in the anteroposterior direction , which coincides well with the mechanical anisotropy of the tissue (Kang et al, 2000a;Singh and Detamore, 2008).…”
Section: Organization and Distribution Of Collagenmentioning
confidence: 93%
“…3 The HIM and TEM images revealed that the fibrous zone was composed of distinct layers of collagen bundles that were approximately orthogonal. This arrangement was also demonstrated in MCC of 8 week rats, 26 immature and mature cynomolgus monkeys, 27 and adult humans. 28 In the present study, the thicker layers were aligned in the anterior-posterior direction, the primary direction of condyle motion and shear loading.…”
Section: Discussionmentioning
confidence: 51%
“…During the growth period, transition from cartilage to bone took place far posterior to and below the top of the condyle. This location corresponds to a region of the articular surface which, even when the mouth is fully opened, is very unlikely to be subjected to compressive stress (Luder and Schroeder 1990). Therefore, the extension of cartilage in the growing condyle does not seem to depend primarily on articular loading, but possibly on other factors such as, for instance, the particular nutritional conditions faced by articular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These animals have been characterized previously with respect to their somatic development (Luder and Schroeder 1990). Likewise, the procedures applied to prepare the left and right mandibular condyles for LM, TEM and SEM have been described in the earlier report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation